Bronchial Asthma among Chechen Republic Schoolchildren: Regional Features - Aset Kh. Ibisheva; Madina R. Shakhgireeva; Linda S. Uspanova; Asya B. Khildikharoeva; Linda V.-M. Dzhabrailova; Kamilla E. Efendieva; Leyla S. Namazova-Baranova (Педиатрическая фармакология, 2024)
Background. The widespread increase in allergic diseases incidence is crucial issue of modern pediatrics. Objective. The aim of the study is to analyze the clinical and epidemiological features of bronchial asthma (BA) in schoolchildren of Chechen Republic.Methods. The study included two stages. 3398 children were surveyed via ISAAC questionnaire at the first stage. All participants were represented by 2 age groups: group 1 — 7–8 years old (n=1331), group 2 — 13–14 years old (n=2067). The second study phase covered clinical and diagnostic examination of children with asthma-like symptoms, enrolled by questionnaire (n=52) — 34 first-graders and 18 eighth-graders.Results. BA symptoms were recorded in 18.4% (625) of children (mostly in the older age group) according to the first stage results. Comparative analysis of the BA symptoms has revealed their prevalence in urban residents (p<0.05). BA was diagnosed in only 46.3% (37) of children during the clinical diagnostic stage. There were no statistically significant differences in age groups at the second stage of the study. No gender differences were revealed at both stages. The highest prevalence of verified BA was recorded in urban residents. Sensitization spectrum analysis in children with isolated BA in Chechen Republic has revealed predominance of domestic allergens sensitivity (house dust mites — D. pteronyssinus, D. farinae) and allergic rhinitis to pollen (ragwort, herd grass).Conclusion. Thus, our study results (according to the ISAAC program) have shown high prevalence of BA symptoms in schoolchildren of Chechen Republic at the first stage, however, the second stage indicated that allergy diagnosis cannot be based only on the questionnaire data and requires clinical and diagnostic verification. The identified regional features of the sensitization spectrum will allow physicians to perform economically optimal diagnosis of BA in children living in Chechen Republic.